FICTIONALITY IN A POSTMODERN NOVELS (BASED ON THE CREATIVITY OF JASPER FFORDE) - Abdullayeva Yegane Atamoglan (International Journal of Innovative Technologies in Social Science, 2020)
In “The Postmodern Condition”, F. T. Lyotard argues that the logos is a myth with the concept of “sunset of metanarrative” and that the world can only be understood as a fictional story. Postmodernist aesthetics refers to this concept and puts forward the idea that the fictitiousness of a character in a literary work fictionizes its state and the events in which he participates. In this regard, in the context of the literary work, real space and characters are fictitious. Fictionality realizes in different ways, and we can see this in the analysis of British writer Jasper Fforde’s novels “Thursday Next”.